Micro-foundational ambidexterity and multinational enterprises: A systematic review and a conceptual framework - Christofi, Michael; Vrontis, Demetris; Cadogan, John W. (My University, 2021)
During the past decade, ambidexterity research has broadened from its traditional macro-level focus to examine the micro-level perspectives of ambidexterity on various settings. The authors systematically review and critically appraise the literature of ambidexterity from a micro-foundational perspective, within the context of Multinational Enterprises (MNEs). By synthesizing the review findings, the authors develop a comprehensive framework that maps extant literature within and across various disciplines and multiple levels of analysis. As part of their review, the authors also identify and discuss important emerging themes and fruitful areas for future research and present the implications to both research and management practice.
Keywords: Conceptual framework; Micro-foundations of ambidexterity; Multinational enterprises; https://www.scopus.com/record/display.uri?eid=2-s2.0-85072605141&origin=resultslist&sort=plf-f&src=s&sid=0ef408aa3ee9ebda9b14edeca811ba74&sot=b&sdt=b&s=DOI%2810.1016%2Fj.ibusrev.2019.101625%29&sl=34&sessionSearchId=0ef408aa3ee9ebda9b14edeca811ba74#:~:text=Multinational%20enterprises%3B-,Systematic%20review,-SciVal%20Topics